DETERMINAN KELELAHAN KERJA KARYAWAN PADA SALAH SATU PERUSAHAAN FAST FOOD DI INDONESIA TAHUN 2022 - Dina Amalia (2022)
Work fatigue is a problem that often occurs in workers caused by many factors. Work fatigue can have an impact on discomfort, decreased performance, and the potential for work errors. The purpose of this study was to analyze the determination of work fatigue in warehouse employees of PT Azka Cahaya Putera. The method was quantitative analytic with a cross-sectional study design. The subjects were all warehouse employees (production and logistic) at PT Azka Cahaya Putera with a total of 85 people using the total sampling method. The statistical test used is the Chi Square test and Fisher Probability Exact Test. The results showed a significant association between smoking habits (p-value=0,021; POR=9,06), sleep duration (p-value=0,041; POR=3,11), workload (p-value=0,038; POR=3,11), and work duration (p-value=0,021; POR=9,06) with work fatigue. Therefore, employees are advised to reduce cigarette consumption, regulate sleep patterns, and take time to stretch while working so it does not cause stiffness and keep the body fit while working.